KHAN ACADEMY Y EL DESARROLLO DE HABILIDADES COGNITIVAS EN LOS ESTUDIANTES DE LA CARRERA DE PSICOLOGIA DE LA UNIVERSIDAD TECNICA DE BABAHOYO, PERIODO ACADEMICO OCTUBRE 2023 – MARZO 2024 - OLIVO POZO PATRICIA GEORDANA (2024)
The study focuses on determining how Khan Academy impacts the development of cognitive skills in Psychology students at the Technical University of Babahoyo. A mixed approach (qualitative and quantitative) with an exploratory descriptive scope was used. The sample consisted of 515 students out of a population of 647. Surveys and observation were used as techniques, questionnaires and observation sheets as data collection instruments. The results revealed that Khan Academy offers structured and varied tools that promote cognitive development, understanding, and strengthening skills in Psychology students. A positive correlation was observed between frequent use of the platform and the strengthening of cognitive skills. However, challenges were identified, such as a lack of motivation to continue using the platform and the need to adapt the content to the specific needs of Psychology courses. Finally, the study highlights the potential of Khan Academy as a complementary resource in the academic training of Psychology students, although it also highlights the importance of addressing the challenges and barriers identified.